Private property and Mennonites are major drivers of forest cover loss in central Yucatan Peninsula, Mexico. (December 2017) - Ellis, Edward A.; Romero Montero, José Arturo; Hernández Gómez, Irving Uriel; Porter-Bolland, Luciana; Ellis, Peter W.
Abstract: The role of land tenure and Mennonites as drivers of deforestation in the Central Yucatan Peninsula has not been empirically assessed. We evaluate different drivers and their relationship to forest cover change between 1986 and 2015 and assess how land tenure and Mennonite communities impact forest cover loss in the Municipality of Hopelchen, Campeche, Mexico. This study shows that forest cover loss has increased in the last decade (2005–2015), and that land tenure regime type is associated with this loss. Throughout the study period, statistical comparisons show rates of forest cover loss were significantly higher in private and federal property compared to forests in ejidos (communal property). Forest cover loss in Mennonite private property was also significantly higher than in non-Mennonite owned private property. The role of land tenure and the expansion of the agroindustrial production model as major drivers of forest cover loss in the region provide important insight into developing municipal land use plans and conservation strategies to reduce deforestation. Programs, incentives and policy directed towards forest conservation in the region that typically target ejido communities, will need to consider the growing trend of private property expansion within federal lands and work more closely with private property owners including Mennonite communities if deforestation reduction programs are to be successful.